Vigilantism and “Plastic Wrap Civil Justice” in 2022 during the Russo-Ukrainian War - Teixeira da Silva Jaime A. (2024)
The aim of the article is to present the results of research and observations related to the phenomenon of vigilantism in the context of military operations in Ukraine.